When Do Nations Tax? The Adoption of Property Tax Codes by First Nations in Canada - Donn. L. Feir; Maggie E. C. Jones; David Scoones (Institute of Labor Economics (IZA), 2022)
Recent changes in Canadian legislation have enabled First Nations to adopt property taxation and other forms of taxation on reserves, thereby allowing them to directly finance their local governments through local tax revenues. In this paper, we compile data on the passage of First Nations tax laws over a thirty year period from a centralized national database on First Nations by-laws, the First Nations Gazette. We combine these data with additional sources to analyze the factors that are associated with First Nations exercising their taxation authority. We find evidence of geographic policy diffusion consistent with First Nations learning from their neighbours and direct evidence that formal educational and institutional resources are important correlates of tax law adoption. Understanding this process informs the broader literature on the evolution of taxation structures and local political incentives, and may contain important lessons for Indigenous tax jurisdiction in other contexts. It is also a critical first step towards assessing the long-term consequences of First Nations' new fiscal powers.
Keywords: H11; H12; H71; P48; 330; state evolution; First Nations; Indigenous; taxation; property; public finance